Seneca Valley Virus Exploits TEM8, a Collagen Receptor Implicated in Tumor Growth - Evans, David J.; Wasinger, Alexa M.; Brey, Robert N.; Dunleavey, James M.; St. Croix, Brad; Bann, James G. (Frontiers in Oncology, 2018)
Recent studies reveal that Seneca Valley Virus (SVV) exploits tumor endothelial marker 8 (TEM8) for cellular entry, the same surface receptor pirated by bacterial-derived anthrax toxin. This observation is particularly significant as SVV is a known oncolytic virus which selectively infects and kills tumor cells, particularly those of neuroendocrine origin. TEM8 is a transmembrane glycoprotein that is preferentially upregulated in some tumor cell and tumor-associated stromal cell populations. Both TEM8 and SVV have been evaluated for targeting of tumors of multiple origins, but the connection between the two was previously unknown. Here, we review currently understood interactions between TEM8 and SVV, anthrax protective antigen (PA), and collagen VI, a native binding partner of TEM8, with an emphasis on potential therapeutic directions moving forward.